Mapping of the distribution and development of phytopathogens in wheat and barley by the NextGIS application - О. Yu. Kremneva; I. A. Kostenko; A. A. Pachkin; R. Yu. Danilov; A. V. Ponomarev; Yu. S. Kim (Зерновое хозяйство России, 2020)
There have been carried out the route surveys to assess the development and distribution of the main pathogens of wheat and barley in 57 districts ofKrasnodar,StavropolTerritoriesand Rostov Region. The collection, organization and analysis of information on the damage degree of the production and breeding sowings of these grain crops by the main pathogens was conducted using a single spatial information environment designed by the Russian company “NextGIS”. During the field surveys, there have been included the data on the resistance to causative agents of yellow leaf spot of wheat, wheat Septoria leaf spot, powdery mildew on wheat and barley, rust diseases on wheat and barley, net spot of barley, and brown spot of barley into the program. In addition, while filling in the survey card, there were taken into account the date and time of the assessment, the phase of development of the grain crop, the variety; there was carried out a photographic fixation of the examined plants. In the field, there was used the freely distributed NextGIS Mobile software, installed on mobile digital devices (smartphones) running by the Android operating system. According to the results of field surveys using the NextGIS QGIS full-featured desktop geographic information system there were prepared thematic cartographic materials of the main wheat and barley pathogens in the southern region ofRussia. The collected long-term data of phytosanitary surveys will allow conducting a temporary analysis of the spatial distribution of pathogens in the studied area. This information can be useful for specialists dealing with plant protection, for employees of breeding institutions who develop varieties resistant to economically significant diseases of grain crops. The data can be used also by a wide range of specialists engaged in plant breeding who conduct field surveys and account any parameters of plant conditions, harmful facilities and the environment, as well as by the consumers of such information.